Conservation of Piping Plover ( Charadrius melodus) in North America: science, successes, and challenges 1 This review is part of the virtual symposium “Flagship Species – Flagship Problems” that deals with ecology, biodiversity and management issues, and climate impacts on species at risk and of Canadian importance, including the polar bear ( Ursus maritimus), Atlantic cod ( Gadus morhua), Piping Plover ( Charadrius melodus), and caribou ( Rangifer tarandus). - Gratto-Trevor, C.L.; Abbott, S. (Canadian Journal of Zoology, 2011)
There are only about 8000 Piping Plovers ( Charadrius melodus Ord, 1834) in existence. Because they depend on environments that are under intense human pressures and controls in both their breeding and wintering grounds, these birds and their habitats are highly managed in many areas across their range. Efforts to recover this endangered and threatened species have engaged thousands of people from Newfoundland to the Caribbean, and have provoked a ground-swell of public support and, at times, fury, as well as a considerable body of research. Although populations have increased substantially in the U.S. Atlantic and U.S. Great Lakes, this is not true of all regions. Significant issues still exist with respect to the efficacy of predator management; need for more accurate model input information; effects of climate, pollutants, and water management; habitat loss and degradation from recreation and development; and whether the cost and effort of management for this species can be maintained or increased where needed.